Análisis de la Cadena de Valor en las Estructuras Productivas de Uchuva y Tomate de Árbol en la Provincia de Sumapaz y el Distrito Capital - Orjuela Castro, Javier Arturo; Castañeda Calderón, Camilo Andrés; Castañeda Calderón, Camilo Andrés; Calderón, María Eugenia (Ingeniería, 2007)
Model that is used to analyze companies competitive advantages is “the chain of value analysis”, but, if de problem is to analize agroindustrial products, the chain of value must be analyzed across the whole chain of interchange of value. The research, which results are reported in this paper, looked for identify distribution channels of products, the structure of the chain of value and the utility for uchuva and tamarillo agroindustrial chain, in the Sumapaz’s province. The costs were established in the chain and the structure of aggregation of value. Six distribution channels were identified and for each of them the usefulness was established for each of the actors in it.